1996
DOI: 10.1128/jb.178.11.3072-3076.1996
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression in early-stationary-phase nutrient broth cultures of Salmonella typhimurium and Escherichia coli is genus specific and not regulated by sigma S

Abstract: We have studied the growth suppression seen in early-stationary-phase LB broth cultures of Salmonella typhimurium. Multiplication of small numbers of an antibiotic-resistant S. typhimurium mutant was prevented when the mutant was added to 24-h cultures of the antibiotic-sensitive parent strain, whereas an antibioticresistant mutant of an Escherichia coli strain added to the same culture grew well. A 24-h E. coli culture produced a similar specific bacteriostatic inhibition against E. coli. In older cultures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…However, the F 0 F 1 proton-translocating ATPase plays a significant role under both aerobic and anaerobic conditions, which could explain why stationary-phase cultures of the unc mutant did not suppress growth. The data support the hypothesis that growth suppression in vitro operates due to the absence of a utilizable carbon source or available electron acceptor, in contrast to previous suppositions (6). The cytochrome d oxidase complex is required under conditions of low oxygen tension (12), as probably occurs in the 24-h-old cultures described here.…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…However, the F 0 F 1 proton-translocating ATPase plays a significant role under both aerobic and anaerobic conditions, which could explain why stationary-phase cultures of the unc mutant did not suppress growth. The data support the hypothesis that growth suppression in vitro operates due to the absence of a utilizable carbon source or available electron acceptor, in contrast to previous suppositions (6). The cytochrome d oxidase complex is required under conditions of low oxygen tension (12), as probably occurs in the 24-h-old cultures described here.…”
contrasting
confidence: 56%
“…Attempts are currently under way to elucidate the mechanisms responsible for this effect. An analogous phenomenon in vitro has been observed with 24-h-old stationaryphase nutrient broth cultures of S. typhimurium (6,8,11). When such cultures are inoculated with small numbers of genetically tagged (antibiotic resistant) but otherwise identical derivatives, the growth of the inoculum is suppressed.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Induction of certain E. coli genes by the addition of supernatant has been described (Baca-DeLancey et al, 1999 ;Li et al, 1997), and growthinhibiting effects of supernatants have been reported in E. coli and other organisms (Barrow et al, 1996 ;Gray et al, 1996 ;Srinivasan et al, 1998). So far, however, the substances involved in these processes have not been identified.…”
Section: Introductionmentioning
confidence: 99%